Cytotoxicity and Cryoprotective Efficiency of Polyvinyl Alcohol Solutions During Freezing of Human Erythrocytes - Hvozdiuk, Yana; Pakhomova, Yulia; Chekanova, Valentina; Kompaniets, Antonina (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):290